Effect and mechanism of Plantaginis Semen polysaccharides on intestinal microecology in rats with hyperuricemia - Zhao, Jing; Fu, Yu; Qiu, Hongbin (Frontiers in Microbiology, 2025)
IntroductionHyperuricemia (HUA) is characterized by metabolic abnormalities in purine metabolism, leading to an excessive accumulation of uric acid in the bloodstream. This condition is not only prevalent but also significantly linked to the exacerbation of various chronic diseases, including renal impairment. Notably, asymptomatic hyperuricemia is frequently associated with inflammatory responses and alterations in intestinal microbiota. Thus, it is imperative to explore effective therapeutic interventions for HUA to mitigate its associated health risks.MethodsThe present study aimed to elucidate the protective effects of Plantaginis Semen polysaccharides (PSP) in a rat model of hyperuricemia induced by adenine (AD) and potassium oxonate (PO) gavage. Over a treatment period of five weeks, the animals received either PSP or allopurinol (AL). Comprehensive assessments were performed, including blood biochemistry analysis, histopathological evaluation, Western blot analyses to investigate the expression levels of key renal transport proteins, as well as 16S rRNA sequencing to explore microbiota shifts.ResultsThe findings demonstrated that PSP significantly decreased serum uric acid (UA) levels and alleviated renal dysfunction through modulation of xanthine oxidase (XOD) and adenosine deaminase (ADA) serum concentrations and the expression of renal transporters, namely glucose transporter protein 9 (GLUT9), urate transporter 1 (URAT1), ATP-binding cassette superfamily member 2 (ABCG2), and organic anion transporter 1 (OAT1). Furthermore, PSP exhibited notable anti-inflammatory properties, reflected in the reduced levels of pro-inflammatory cytokines such as tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β).ConclusionIn summary, the present study substantiates the therapeutic potential of PSP in treating hyperuricemia through its dual action of lowering uric acid levels and imparting anti-inflammatory effects. The observed modulation of gut microbiota further supports the role of PSP in maintaining metabolic homeostasis. Future investigations should focus on the clinical applicability of PSP and elucidate the mechanisms underlying its beneficial impacts on hyperuricemia and associated metabolic disorders.